Penyelesaian Perselisihan Hubungan Industrial melalui Putusan Perdamaian di Pengadilan Hubungan Industrial Pengadilan Negeri Padang Kelas I (A) - Kusmayanti, Hazar; Karsona, Agus Mulya; Fakhriah, Efa Laela (Departemen Hukum Perdata, 2020)
Industrial relations disputes can be resolved through court (litigation) and out of court (non litigation) as stipulated in Law Number 2 of 2016 concerning Industrial Relations Dispute Settlement (PPHI). From the formal legal aspect governing the settlement of industrial relations disputes is the Law Civil Procedure that applies in the General Court, which is usually complicated and long. Usually for litigation at the District Court level, at least the workers/litigants must meet for 8 to 10 days. Padang District Court in the IA Class in order to achieve the principle of Civil Procedure Law Fast, Simple and Low Cost made a breakthrough with the success in bringing a decision on peace in industrial relations disputes in the past 4 years. The author is interested whether this Peace ruling does not contradict Article 4 of PERMA Number 1 of 2016 and does not conï¬‚ ict with statutory regulations and has permanent legal force. The method used in this research is normative juridical analysis of facts that exist systematically. The results of the research and discussion showed that Article 4 of PERMA Number 1 of 2016 is doubly meaningful, so that the Peace Decision in the Padang District Court of Class IA is not in conï¬‚ ict with the laws and regulations and has permanent legal force. The factors causing peace in the Padang Industrial Relations Court, namely Article 4 PERMA Number 1 of 2016 has a double meaning, so that the Padang Industrial Relations Court refers to Article 130 HIR, there is pressure on the bipartite process, mediation in the employment service is less than optimal, the parties those who disputed want peace to be carried out in the industrial relations court, the panel of judges considered that disputes were very possible to be carried out peacefully, and to reduce the accumulation of cases in the court.